Enhancing Qur’anic Memorization through the Application of the Talaqqi Method in Tahfidz Education - Jesica Novitriani; Ali Muhdi (Indonesian Academy of Social and Religious Research (IASRR), 2025)
The effectiveness of a Qur'anic memorization program is significantly influenced by the methodology employed to ensure both the accuracy and sustainability of memorization. At the Ar-Rohman Orphanage in Purbalingga, the talaqqi method, where students attentively listen to the teacher's recitation and reproduce it with proper tartīl and tajwid, is the principal pedagogical approach. This study aims to examine the implementation of the talaqqi method in enhancing students' memorization proficiency and to identify key supporting and inhibiting factors. This article employs a qualitative case study design, data were gathered through observation, interviews, and documentation and subsequently analyzed through systematic data reduction, display, and conclusion drawing. The findings reveal that the talaqqi method is operationalized in three main stages: preparation (prayers, mushaf readiness, murājaʿah), implementation (memorization submission, recitation correction, class supervision), and evaluation (daily, per juzʾ, and periodic five juzʾ reviews). Strategies for memorization retention include individual takrīr, incorporation into daily prayers, and peer collaboration. Supporting factors consist of a spiritually conducive environment, encouragement from caregivers and peers, and sufficient infrastructure, while challenges include difficulties in tajwīd, articulation (makhārij al-ḥurūf), and long-term retention. The talaqqi method is thus validated as an effective technique for fostering high-quality Qur'anic memorization.